Armed conflict in Guatemala: historical reconstruction and collective memory of the Mayan Chuj people - López Bracamonte, Fabiola Manyari (Universidad Pedagógica y Tecnológica de Colombia, 2021)
At the beginning of 1980, one of the most intense and atrocious military repressions in the long history of political violence of Guatemala was unleashed. Within the framework of the disputes of the Cold War, the Mayan peoples became internal enemies of national projects and, therefore, they were the targets of strategies of terror, forcing them to migrate in order to protect their physical and cultural lives. Although the state violence marked a rupture, experiences such as those of the Mayan Chuj people are an example of physical and symbolic resistance. With the aim of contributing new data for analysis and reflection concerning the violence exerted over the Mayan peoples in Guatemala, this article conducts a historical reconstruction of those events, revisiting aspects of the historical and collective memory of the Mayan Chuj people. To this end, the quality of the political, social and cultural interactions of the essential aspects that unleashed, accompanied and marked the context of the armed conflict, the forced displacement, protection and refuge in Mexico are analysed, as well as the return and repatriation of the Mayan Chuj people to Guatemala.